FRACTIONAL FACTORIAL DESIGNS 1/32 (45) IN BLOCKS OF SIXTEEN UNITS - Conagin, Armando; AmbrÃ³sio, LuÃs Alberto (REVISTA DE AGRICULTURA, 2015)
FRACTIONAL FACTORIAL DESIGNS 1/32 (45) IN BLOCKS OF SIXTEEN UNITS